Peran Keselamatan dan Kesehatan Kerja (K3) Dalam Meningkatkan Kinerja Dan Loyalitas Karyawan Sebuah Studi Literatur - Permadi, Indra; Lamo, Muh. Luthfi; Anisa, Anisa; Khairati, Miftah Isra; Rahman, Ahmad Nashiruddin Mushoddiq (Jaanur Elbarik Indonesia, 2025)
This study aims to examine the role of occupational safety and health (OSH) in improving employee performance and loyalty through a literature review approach. The method used is a descriptive qualitative analysis of various sources, including scientific journals and research reports. This review analyzes thirteen national and international scientific articles published between 2020 and 2025. The results show that the implementation of OSH has a positive effect on employee performance and loyalty. An optimal implementation of OSH can create a safe and healthy work environment, reduce accident rates, and increase efficiency and organizational commitment. Therefore, OSH serves as a strategic factor in enhancing company performance and competitiveness..